General Characteristics, Distribution, and Ecology of Rodents in the Samarkand Region - Umarov Mansur Normamatovich; Utemuratova Gulshirin Najimatdinovn (American Journal of Biodiversity, 2025)
The article examines the general characteristics, distribution, and ecology of rodents in the Samarkand region. Within the scope of the research, the species of synanthropic rodents widespread in the region, their biological characteristics, reproduction patterns, and the damage they cause to the economy were analyzed. It was determined that the Norway rat (Rattus norvegicus), Turkestan rat (Rattus turkestanicus), house mouse (Mus domesticus), and yellow ground squirrel (Citellus fulvus) species are widely distributed in the region. Statistical analyses showed the presence of 23-45 rat colonies per hectare in major trading areas of Samarkand district. A single rat consumes 7-15 kg of food per year and stores 10-25 kg of grain and other products in its nest. In 2024, 755 citizens were bitten by rats in the region. Rodents cause significant economic damage by destroying agricultural crops, spreading infectious diseases, and disabling communication systems. The article covers comprehensive control measures against rodents and ecological monitoring issues